Global research trends on drug interactions with direct oral anticoagulants: A comprehensive bibliometric analysis - Ivan Henao-Torres, Antistio Alviz-Amador, Nathalie Gómez-Sánchez (Journal of Applied Pharmaceutical Science, 2025)
This study presents a bibliometric analysis of global research on drug interactions involving direct oral anticoagulants (DOACs), mapping field development, identifying hotspots, and highlighting trends to guide future studies and improve clinical safety. Effective management of DOAC interactions is critical in clinical and public health. Publications on DOAC interactions from 2011 to 2023 were retrieved from Scopus and analyzed using VOSviewer, Google Colab, and the R package bibliometrix, enabling performance assessment and science mapping. Analysis of 345 publications from 45 countries reveals a significant rise in DOAC research, led by contributions from North America, Europe, and East Asia, with the United States, Germany, and Japan producing the most publications. Notable institutions include Inserm, Harvard Medical School, and McMaster University, alongside industry leaders such as Daiichi Sankyo, Bayer AG, and Boehringer Ingelheim, underscoring academia-industry partnerships. Keyword analysis shows that key research themes identified are “Anticoagulant,” “Rivaroxaban,” “Atrial fibrillation,” and “Drug interaction.” Recent studies focus on physiologically based pharmacokinetic (PBPK) modeling and interactions within oncology and COVID-19 treatment, highlighting challenges in managing drug–drug interactions (DDIs) in polypharmacy. This analysis uncovers how pharmacokinetic and pharmacodynamic interactions contribute to improving the safety of DOACs, offering insights that can guide clinical approaches and formulate public health policies.
Keywords: Drug interaction, DOAC, anticoagulant, PBPK, clinical practice, bibliometric analysis